Peran Sucralfate Topikal dalam Mengurangi Nyeri Pasca-Hemoroidektomi - Jessica Nathania; Shania Sutanto Jaya; Anthony Yauwono (PT Kalbe Farma Tbk., 2024)
Hemorrhoids are one of the most common perianal cases and may cause lower gastrointestinal bleeding. Most cases can be treated with medications and/or simple procedures. Surgical intervention is required in advanced stages or complicated cases. However, this procedure is often associated with postoperative pain. Topical sucralfate is known to reduce postoperative pain.